Low Concern Rate With Oral Health and Associated Factors Among Older Persons: A Cross-Sectional Study - Ana Flávia Leite Pontes; Juliana dos Santos Feijo; Nathália Prigol Rosalen; Natália Rigon Scalco; Paulo Roberto Grafitti Colussi; Francisco Wilker Mustafa Gomes Muniz (Geriatrics, Gerontology and Aging, 2024)
OBJECTIVE: This study aimed to assess the prevalence of concern with oral health and associated factors among older adults. METHODS: Individuals aged ≥60 years were included from the cities Cruz Alta and Veranópolis, Brazil. Oral health examination and a structured questionnaire were applied in 569 individuals. The main outcome was concern with oral health (yes or no), which was determined by a validated questionnaire. Uni- and multivariate analyses were conducted by Poisson regression with robust variance to assess the association between outcome and independent variables. RESULTS: The prevalence of concern with oral health was 30.58% (n = 174). Non-white individuals presented significantly higher prevalence ratio (PR) of being concerned about their oral health (PR = 1.28; 95% confidence interval [CI] 1.01–1.62). Individuals with medium or high level of education, not retired and without any health problems presented higher PR of being concerned with their oral health when compared to their controls (p < 0.05). Moreover, those that reported toothbrushing frequency ≥ 2 times/day (PR = 1.58; 95%CI 1.01 – 2.48) and non-edentulous (PR = 1.50; 95%CI 1.12–2.01) also presented higher PR of being concern with their oral health. Older adults that were not concerned with tooth alignment (PR = 0.57; 95%CI 0.44 – 0.74) or tooth color (PR = 0.41; 95%CI 0.31 – 0.54) demonstrated lower concern with their oral health. CONCLUSION: Prevalence of concern with oral health among the older adults was low and associated with non-white individuals, medium and high level of education, individuals not retired, absence of health problems, higher toothbrushing frequency, mild temporomandibular disorder (TMD) and non-edentulism. Additionally, concern with esthetical aspects may be related with this outcome.